2019
DOI: 10.3847/1538-3881/ab1260
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Debris Disk Variability: Exploring the Diverse Outcomes of Large Asteroid Impacts During the Era of Terrestrial Planet Formation

Abstract: The most dramatic phases of terrestrial planet formation are thought to be oligarchic and chaotic growth, on timescales of up to 100-200 Myr, when violent impacts occur between large planetesimals of sizes up to protoplanets. Such events are marked by the production of large amounts of debris, as has been observed in some exceptionally bright and young debris disks (termed extreme debris disks). Here we report five years of Spitzer measurements of such systems around two young solar-type stars: ID8 and P1121. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 87 publications
4
56
0
Order By: Relevance
“…In this case, the lack of a substantial inner disk eliminates some of the proposed mechanisms involving accretion (Bouvier et al 2013) or vertical structures in a disk (Ansdell et al 2016b). Impact disruption of asteroidal bodies or giant impacts during the final phase of rocky planet formation (Morbidelli & Raymond 2016) have been invoked to explain warm dust around 30-50 Myr-old RZ Piscium, the 25 Myrold β Pictoris Moving Group member HD 172555 (Johnson et al 2012), and ID8, a star with a rapidly time-varying excess in the ∼35 Myr cluster NGC 2547 (Su et al 2019). Something analogous to these impact-driven disks might explain the excess infrared emission of 125 Myr-old HD 240779.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In this case, the lack of a substantial inner disk eliminates some of the proposed mechanisms involving accretion (Bouvier et al 2013) or vertical structures in a disk (Ansdell et al 2016b). Impact disruption of asteroidal bodies or giant impacts during the final phase of rocky planet formation (Morbidelli & Raymond 2016) have been invoked to explain warm dust around 30-50 Myr-old RZ Piscium, the 25 Myrold β Pictoris Moving Group member HD 172555 (Johnson et al 2012), and ID8, a star with a rapidly time-varying excess in the ∼35 Myr cluster NGC 2547 (Su et al 2019). Something analogous to these impact-driven disks might explain the excess infrared emission of 125 Myr-old HD 240779.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Present-day observations are limited to observing the micronsized (e.g., Lisse et al 2012Lisse et al , 2017 to millimeter-sized (MacGregor et al 2019) dust contents of extrasolar disks. Indirect observations of macroscopic objects and their volatile contents in debris disks can be obtained through the massive amounts of dust produced by their collision with each other (Meng et al 2014;Su et al 2019), their presence around young stars (Chen et al 2006), or sometimes by their transit of stars (Rappaport et al 2018), but observing and obtaining the physical properties and volatile contents of specific bodies from other stars has remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the stopping time is t e = sρ d csρ for dust particles with size s < 9 4 λ (Epstein regime in Weidenschilling, 1977). For particles with s = 1 mm this time is 1.53 yr and it increases with s. Even this value is significantly more than the destruction time obtained in Su et al (2019).…”
Section: Model Rationalementioning
confidence: 88%
“…1 the formation of the planetary system may be accompanied with catastrophic collisions of planet embryos or planetesimals. In paper Su et al (2019) was shown the formation of cloud of small dust may take days to a month depending on the velocity of impact. But the conclusions regarding the cascade destruction of colliding bodies are made for the models without gas; however, they are applicable to our model.…”
Section: Model Rationalementioning
confidence: 99%
See 1 more Smart Citation